Profit Sensitivity in the Decision-making Process - Ofilean, Dimi; Topor, Dan Ioan; Paschia, Liliana (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
Projections on the profitability of an entity is a prerequisite impact assessment of implementing various management strategies. The literature did not include a model sensitivity analysis in terms of profit margin of safety modification and safety coefficient. This article aims to explicit solutions for identifying the factors that influence the sensitivity of profit, the proposed analytical models to change the margin of safety (physical and value) and coefficient of safety. The model allows the determination of limits that can increase or decrease sales costs so that the company remains profitable, ie to be able to maintain an adequate level of profit. This analysis allows knowing the influence of each factor in the evolution of the profitability of the entity, allowing managers to adopt the right decisions based on the importance of the influence of the analysis results of the entity. To facilitate understanding of the proposed analytical model is presented a case study.